BIBLIOMETRIC ANALYSIS OF ACADEMIC RESEARCH ON MONEY POLITICS IN INDONESIA: CHALLENGES AND INTERESTING ISSUES - Purwaningsih, Titin -; Widodo, Bambang Eka Cahya; Tunjung, Sulaksono; Widayat, Rossi Maunova; Pahlevi, M Edward Trias; Amrurobbi, Azka Abdi (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
This study aims to describe the issue of money politics in elections in Indonesia. The method used in this study is qualitative, using a literature review. The research data is sourced from the Scopus database in July 2023, using the keywords politics elections, and money. Data analysis used Bibliometric Biblio Shiny R 4.3.1 and Scopus data analysis. The research results show many issues in studying money politics in Indonesia from various perspectives. Aspects of power, money, and elections are three keywords that influence the practice of money politics in Indonesia. Then in terms of actors, money politics in Indonesia is driven by political parties and candidates driven by the capitalist elite network. Some of the significant issues above the opportunities for money politics can be examined in the future through various fundamental perspectives. The relationship between patrons and clients and networks between election participants and elite financier networks (konglongmerat) is a challenge for further research. This research contributes to providing space and new perspectives in studying the practice of money politics in Indonesia.